2010
DOI: 10.1187/cbe.10-02-0012
|View full text |Cite
|
Sign up to set email alerts
|

Using Invention to Change How Students Tackle Problems

Abstract: Invention activities challenge students to tackle problems that superficially appear unrelated to the course material but illustrate underlying fundamental concepts that are fundamental to material that will be presented. During our invention activities in a first-year biology class, students were presented with problems that are parallel to those that living cells must solve, in weekly sessions over a 13-wk term. We compared students who participated in the invention activities sessions with students who part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…However, the current implementation did not have the time to emphasize the development of strategic knowledge and scientific dispositions (Gresalfi & Cobb, 2006). Taylor, Smith, van Stolk, and Spiegelman (2010) found that students who received a full course of inventing activities in college-level cell biology were more able to generate explanations for novel cell phenomena compared to T&P students.…”
Section: Alternative Hypothesesmentioning
confidence: 99%
“…However, the current implementation did not have the time to emphasize the development of strategic knowledge and scientific dispositions (Gresalfi & Cobb, 2006). Taylor, Smith, van Stolk, and Spiegelman (2010) found that students who received a full course of inventing activities in college-level cell biology were more able to generate explanations for novel cell phenomena compared to T&P students.…”
Section: Alternative Hypothesesmentioning
confidence: 99%
“…We did not have sustained direct assessment of learning objectives. Like many other educators, we agreed that these objectives (see Appendix: Table 1, second column) centered on the ability to solve novel problems within our discipline (Taylor, Smith, van Stolk, & Spiegelman, 2010). Unfortunately, our students rarely encountered the opportunity to solve novel problems in their coursework.…”
Section: Introductionmentioning
confidence: 68%
“…Unfortunately, our students rarely encountered the opportunity to solve novel problems in their coursework. Others have noted this problem as well (Jonassen, 2000;Taylor et al, 2010).…”
Section: Introductionmentioning
confidence: 98%
“…A growing body of evidence has documented the benefits of delaying instruction until after an opportunity for exploratory problem solving Kapur, 2010Kapur, , 2011Kapur, , 2012Kapur & Bielaczyc, 2012;Needham & Begg, 1991;Schwartz & Bransford, 1998;Schwartz et al, 2011;Schwartz & Martin, 2004;Taylor et al, 2010). However, the majority of past research comparing an exploreinstruct approach to a conventional instruct-solve approach has used complex problem-solving tasks with adolescents or adults and instruction that included information on solution procedures (Kapur, 2010(Kapur, , 2011(Kapur, , 2012Schwartz et al, 2011;Schwartz et al, 2009;Schwartz & Martin, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of evidence supports the potential of an explore-instruct approach for a wide range of topics, including elementary mathematics (DeCaro & Rittleohnson, 2012), middle-school science (Schwartz et al, 2011), high-school statistics (Kapur, 2012), analogical reasoning (Needham & Begg, 1991), cell functioning (Taylor, Smith, van Stolk, & Spiegelman, 2010) and psychology (Schwartz & Bransford, 1998). Experimental studies on the timing of instruction relative to solving unfamiliar problems provide the most direct evidence for the effectiveness of an exploreinstruct approach.…”
mentioning
confidence: 99%